Recent advances in laboratory education research - Agustian Hendra Y. (Chemistry Teacher International)
This review synthesizes recent advancements in laboratory education research in university chemistry over the past decade, from 2014 to 2024. It focuses on three key areas: evidence-oriented teaching practices, student learning outcomes and processes, and progressive curriculum development. The paper highlights the growing emphasis on evidence-based approaches to laboratory instruction, the multifaceted nature of student learning in the laboratory, and the importance of designing laboratory curricula that ensure progression and congruence across study programs. The review instantiates how evidence-oriented teaching practices have led to a shift in focus from theory to practical techniques. It explores the diverse learning outcomes associated with laboratory work, including experimental competencies, conceptual understanding, and affective aspects such as identity development and self-efficacy. The paper also introduces a comprehensive framework for assessing student learning in laboratories, integrating cognitive, conative, affective, psychomotor, social, and epistemic domains. Furthermore, the review examines approaches to curriculum development that emphasize scaffolding, progression, and alignment between various curricular elements. It presents models for developing experimental design competence and ensuring congruence in laboratory curriculum development. The paper concludes by acknowledging the persistent gap between research and practice in laboratory education and calling for continued efforts to bridge this divide.